WORKSHOP PERSONAL DEVELOPMENT DALAM PENINGKATAN KEPERCAYAAN DIRI BERKOMUNIKASI PADA ANAK BINAAN YAYASAN INSAN SAPA DHUAFA: Personality Development Training In Increasing The Self-Confidence Of Communication In Children In Sapa Dhuafa Research Children's Foundation - Pramelani; RR Roosita Cindrakasih; Taqwa Sejati; Muhamad Jejen Jaelani (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
the children assisted by the Insan Sapa Dhuafa Foundation which trains self-confidence focused on communication practices. Children never get insight into personal development in communication. Therefore, with the conditions experienced by the partners, this community service activity has the theme "Self-Development Workshop for Fostered Children of the Insan Sapa Dhuafa Foundation". The method used consists of 3 stages namely; (1) The preparatory stage includes identifying problems, applying for permits to partners and finding sponsors; (2) Stages of implementing community service activities; (3) Evaluation stage, giving a questionnaire to find out understanding of knowledge about increasing communication trust. The results obtained from this community service are an increase in knowledge and communication skills for participants which are useful in supporting their activities both within the Foundation and at school. In addition, partners are satisfied with the results of these activities because they provide positive energy for the dhuafa children under their care.